More severe hypoxemia is associated with better subjective sleep quality in obstructive sleep apnea. Issue 1 (December 2015) - Wu, Meng-Ni; Lai, Chiou-Lian; Liu, Ching-Kuan; Liou, Li-Min; Yen, Chen-Wen; Chen, Sharon; Hsieh, Cheng-Fang; Hsieh, Sun-Wung; Lin, Feng-Cheng; Hsu, Chung-Yao
Abstract Background Perceived sleep quality may play an important role in diagnosis and therapy for obstructive sleep apnea (OSA). However, few studies have assessed factors that are associated with perceived sleep quality in OSA patients. Hypoxemia depresses the central nervous system and attenuates the perceived respiratory load in asthmatic patients. This study aimed to investigate the factors related to perceived sleep quality, focusing on the role of hypoxemia. Methods Polysomnography studies of 156 OSA patients were reviewed. Traditional polysomnographic parameters, including parameters of oxy-hemoglobin saturation (SpO2), were calculated, and the sleep questionnaire and scales were used. Considering the possible pitfalls of absolute values of SpO2 and individualized responses to hypoxemia, the amplitude of desaturation was further computed as "median SpO2 minus lowest 5 % SpO2 "and "highest 5 % SpO2 minus median 5 % SpO2". Correlations between these parameters and perceived sleep quality, represented as the Pittsburgh sleep quality index (PSQI), were performed. Multiple linear regression analysis was also conducted to investigate the factors associated with the PSQI. Results Although the PSQI was not correlated with the apnea-hypopnea index (r = −0.113, p  = 0.162) and oxygen desaturation index (r = −0.085, p  = 0.291), the PSQI was negatively correlated with "median SpO2 minus lowest 5 % SpO2" (r = −0.161, p  = 0.045). After adjusting for age, total sleep time, the periodic limb movements index, tendency of depression, and the lowest 5 % SpO2, the "median SpO2 minus lowest SpO2" was still a significant predictor for a lower PSQI (β = −0.357, p  = 0.015). Conclusions More severe hypoxemia is associated with better perceived sleep quality among OSA patients. This paradox may be associated with hypoxemia-related impairment of perception. The effect of hypoxemia did not appear to be significant in relatively mild hypoxemia but become significant in severe hypoxemia." Median SpO2 minus lowest 5 % SpO2" may also be a better predictor of perceived sleep quality than the apnea-hypopnea index because of the disproportionate effects of hypoxemia. Additionally, further studies are necessary to confirm the role of hypoxemia on perceived sleep quality and identify the possible threshold of hypoxemia in OSA patients.